2014
DOI: 10.1002/anie.201406630
|View full text |Cite
|
Sign up to set email alerts
|

Proton‐Transfer Polymerization (HTP): Converting Methacrylates to Polyesters by an N‐Heterocyclic Carbene

Abstract: A new polymerization termed proton (H)-transfer polymerization (HTP) has been developed to convert dimethacrylates to unsaturated polyesters. HTP is catalyzed by a selective N-heterocyclic carbene capable of promoting intermolecular Umpolung condensation through proton transfer and proceeds through the step-growth propagation cycles via enamine intermediates. The role of the added suitable phenol, which is critical for achieving an effective HTP, is twofold: shutting down the radically induced chain-growth add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 132 publications
0
39
0
Order By: Relevance
“…[193] In a recent addition, TPT was found to efficiently catalyze the conversion of dimethacrylates into unsaturated polyesters of Mw up to 28,400 g.mol -1 and Đ = 1.1-1.9, in toluene at 80 °C (Scheme 67). [194] This reaction was thought to involve the initial conjugate addition of TPT onto the monomer, forming the triazolium enolate 35 (Scheme 67). Upon proton transfer, the resulting nucleophilic diaminoalkene 36 could react in a 1,4-fashion with another monomer molecule to yield the new triazolium enolate 37.…”
Section: Polymerizations Directly Induced By Organic Initiatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…[193] In a recent addition, TPT was found to efficiently catalyze the conversion of dimethacrylates into unsaturated polyesters of Mw up to 28,400 g.mol -1 and Đ = 1.1-1.9, in toluene at 80 °C (Scheme 67). [194] This reaction was thought to involve the initial conjugate addition of TPT onto the monomer, forming the triazolium enolate 35 (Scheme 67). Upon proton transfer, the resulting nucleophilic diaminoalkene 36 could react in a 1,4-fashion with another monomer molecule to yield the new triazolium enolate 37.…”
Section: Polymerizations Directly Induced By Organic Initiatorsmentioning
confidence: 99%
“…This new step-growth polymerization, referred to as proton (H) transfer polymerization (HTP), was proposed to proceed by repeated conjugate addition / proton transfer / conjugate addition / proton transfer/ NHC release sequences. [194] Deactivation of the NHC by intra-molecular C-H insertion of the carbene center into a CH3 Mes was proposed to account for the inactivity of the diazepinium-based carbene (Scheme 69). [18,196] Scheme 69.…”
Section: Polymerizations Directly Induced By Organic Initiatorsmentioning
confidence: 99%
“…Similarly, it was recently demonstrated that MMA can be oligomerized in a more controlled manner in the presence of alcohols or hydroxyl-functionalized polyether using 5-tBu in DMF at 25 ∘ C. 89 Finally, it was also shown that dimethylacrylate (DMA) can be converted to unsaturated polyester (Scheme 14) by application of TPT at 80 ∘ C in toluene in the presence of aromatic alcohols (radical scavengers). 90 By this method, polymers with considerable molecular weight were generated (M w = 17 000 g mol −1 , Ð M = 1.9). Mechanistically, this process crucially involves the formation of Breslow-type intermediates after the NHC has added to the double bond, a step for which TPT is commonly a very good choice.…”
Section: Polymerization Of Acrylic Monomersmentioning
confidence: 99%
“…Nucleophilic activation (Scheme ), which consists of the 1,2‐ or 1,4‐addition of the NHC onto saturated or conjugated esters, respectively, has been widely investigated for various NHC‐catalyzed transformations, such as the transesterification reaction, the Morita–Baylis–Hillman reaction,23 and the dimerization of methyl methacrylate (MMA)24, 25 or the tetramerization of methyl acrylate (MA) 26. The catalytic step‐growth polymerization of bis(meth)acrylate monomers, by iterative dimerization of methacrylate moieties, has been recently applied as a means to achieve unsaturated poly(esters) 27…”
Section: Introductionmentioning
confidence: 99%
“…[26] The catalytic step-growth polymerization of bis(meth)acrylate monomers, by iterative dimerization of methacrylate moieties, has been recently applieda s am eans to achieve unsaturated poly(esters). [27] Interestingly,v arious 1:1o r1 :2 reactiona dducts between aN HC and aM ichael (meth)acrylate acceptor, that is, following an oncatalytic process, have also been reported. [28][29][30] Although all of them involve initial nucleophilic 1,4-addition of the NHC onto the (meth)acrylate, different reactiono utcomes have been eventually observed, depending on the nature of the carbene.…”
Section: Introductionmentioning
confidence: 99%